Essays on the Global Financial Crisis - Hesse, Heiko (International Monetary Fund, 2016)
The Global Financial Crisis has been a watershed event not only for many advanced economies but also emerging markets around the world. This book brings together research and policy work over the last nine years from staff at the IMF. It covers a wide range of issues such as the origins of the financial crisis, the policy response, spillovers and contagion, case studies, bank stress testing, and debt sustainability and sovereign debt restructuring.